2020
DOI: 10.7554/elife.52690
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine 1-phosphate-regulated transcriptomes in heterogenous arterial and lymphatic endothelium of the aorta

Abstract: Despite the medical importance of G protein-coupled receptors (GPCRs), in vivo cellular heterogeneity of GPCR signaling and downstream transcriptional responses are not understood. We report the comprehensive characterization of transcriptomes (bulk and single-cell) and chromatin domains regulated by sphingosine 1-phosphate receptor-1 (S1PR1) in adult mouse aortic endothelial cells. First, S1PR1 regulates NFκB and nuclear glucocorticoid receptor pathways to suppress inflammation-related mRNAs. Second, S1PR1 si… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 72 publications
2
20
0
Order By: Relevance
“…In the intact nerve, in addition to the lymphatic EC cluster (cluster 13, Figure 1A ) identified by marker genes for lymphatic ECs such as Lyve1, Mmrn1, Prox1, and Flt4 ( Supplementary Figure 1 ) (Engelbrecht et al, 2020 ; Fujimoto et al, 2020 ; Wolbert et al, 2020 ), our analysis shows three distinct sub-clusters of blood vessel ECs in the intact nerve not described in the previous studies (cluster 3, 4, and 5, Figure 1A ). All three new EC sub-clusters express classic EC marker genes such as Pecam1/Cd31, Tie1, and Emcn ( Supplementary Figure 2 ) (Zhao et al, 2018 ; Carr et al, 2019 ; Kalluri et al, 2019 ; Toma et al, 2020 ; Wolbert et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the intact nerve, in addition to the lymphatic EC cluster (cluster 13, Figure 1A ) identified by marker genes for lymphatic ECs such as Lyve1, Mmrn1, Prox1, and Flt4 ( Supplementary Figure 1 ) (Engelbrecht et al, 2020 ; Fujimoto et al, 2020 ; Wolbert et al, 2020 ), our analysis shows three distinct sub-clusters of blood vessel ECs in the intact nerve not described in the previous studies (cluster 3, 4, and 5, Figure 1A ). All three new EC sub-clusters express classic EC marker genes such as Pecam1/Cd31, Tie1, and Emcn ( Supplementary Figure 2 ) (Zhao et al, 2018 ; Carr et al, 2019 ; Kalluri et al, 2019 ; Toma et al, 2020 ; Wolbert et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies using scRNA-seq to analyse endothelial cell profiles of specific structures of the blood supply system such as the aorta, the hematopoietic niche, the lymph nodes and the heart, often resulted in the identification of 2–4 sub-clusters of endothelial cells. These studies showed that it can be very difficult to name individual sub-clusters of EC cells because of overlapping expression patterns of key endothelial cell genes (Kenswil et al, 2018 ; Feng et al, 2019 ; Kalluri et al, 2019 ; Engelbrecht et al, 2020 ; Fujimoto et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to regulating glomerular and tubular cells, apoA-I/HDL modulates the phenotype of lymphatic endothelial cells and growth of the lymphatic vascular network [ 76 , 77 ]. S1P/S1PR1 signaling is involved in the regulation of lymphangiogenic and inflammation-related gene expression in lymphatic endothelial cell (LECs) [ 78 ]. We found that IsoLG-modified apoA-I stimulated higher expression of inflammation markers (IL-6, IL-23, CCL21) and S1P related genes (SPHK2, SPNS2) in cultured LECs than unmodified apoA-I.…”
Section: Hdl Modulates Renal Parenchymal Cells and Functionmentioning
confidence: 99%
“…[66] This trend is also observed when restricting analyses to a large artery; scRNA-seq analysis of the adult aorta identified multiple BEC clusters, with expression patterns reflecting specific anatomical locations (i.e., branch points) and suggesting distinct roles in adhesion, signaling, and immune function. [67] Although largescale comparisons across different organs have failed to capture significant heterogeneity among LECs, [64] targeted scRNA-seq of lymph node lymphatic vessels revealed multiple subpopulations that may play distinct roles in neutrophil homing. [68] More examples of EC transcriptional heterogeneity emerge on a frequent basis with new scRNA-seq datasets.…”
Section: Transcriptional Heterogeneity In the Endotheliummentioning
confidence: 99%